Viral Hepatitis E and Chronicity: A Growing Public Health Concern - Thakur, Vikram; Ratho, Radha Kanta; Kumar, Swatantra; Saxena, Shailendra K.; Bora, Ishani; Thakur, Pryanka (Frontiers in Microbiology, 2020)
Hepatitis E viral infection recently emerges as a global health concern. Over the last decade, the understanding of HEV had changed with the discovery of new genotypes like genotype-7 and genotype-8 with associated host and mode of infection. Diversification in the mode of hepatitis E infection transmission through blood transfusion, and organ transplants in contrast to classical feco-oral and zoonotic mode is the recent medical concern. The wide spectrum of infection ranging from self-limiting to acute liver failure is now overpowered by HEV genotype-specific chronic infection especially in transplant patients. This concern is further escalated by the extra-hepatic manifestations of HEV targeting the CNS, kidney, heart, and pancreas. However, with the development of advanced efficient cell culture systems and animal models simulating the infection, much clarity towards understanding the pathogenetic mechanism of HEV has been developed. Also this facilitates the development of vaccines research or therapeutics. In this review, we highlight all the novel findings in every aspect of HEV with special emphasis on recently emerging chronic mode of infection with specific diagnosis and treatment regime with an optimistic hope to help virologists and/or liver specialists working in the field of viral hepatitis.